Iam deperditae, nunc repertae : Trois inscriptions « perdues » aux musées d’Amphipolis et Kavala - Nigdelis, Pantelis; Anagnostoudis, Pavlos (Tekmeria, 2017)
Three inscriptions, considered to be lost, are being re-edited in the present article: (a) the funerary inscription of Ammia from Amphipolis, (b) the funerary stele of Adymos from Eleutheroupolis, and (c) the dedicatory inscription of bishop Alexander which was originally found in Thasos. The three stones were rediscovered in the museums of Amphipolis and Kavala.